Ethical Processes and Dilemmas during Research with Youth on Cyber-Risk - Cavanagh, Jay; Adorjan, Michael; Ricciardelli, Rosemary (Qualitative Sociology Review, 2025)
In this article, we reflect on the ethical processes and dilemmas we encountered in almost a decade of qualitative research with teenagers about digital technologies and cyber-risk. Our research underscores both the opportunities and challenges of teenagers’ engagements with digital technologies, including cyberbullying and image-based sexual harassment and abuse (i.e., non-consensual sexting), on popular social media platforms. Our current research explores teenagers’ experiences with cyber-risk during the COVID-19 pandemic, including managing homeschooling (due to lockdowns), online addiction, mental health challenges, and encounters with disinformation and misinformation. We discuss our experiences with focus group facilitation and one-to-one semi-structured interviews, specifically our reflections on ethical processes encountered in the field, such as fostering rapport with young participants given the significant age gaps and our lack of knowledge at times, regarding digital technologies or topics like image-based sexual abuse. We also discuss our experiences conducting research with teenagers under the new capacity to consent ethical framework, which positions children and youth as often having agency to consent to research independently from their parents or legal guardians. Here, we detail reflections on navigating a new approach and highlight some of the considerations arising from ascertaining assent and consent. Centralizing issues of developing rapport, trust, and ethical processes related to interactional dynamics during interviews, the paper provides insights and possible strategies for those conducting research with children and youth.